2019
DOI: 10.1111/tpj.14437
|View full text |Cite
|
Sign up to set email alerts
|

The apoplastic antioxidant system and altered cell wall dynamics influence mesophyll conductance and the rate of photosynthesis

Abstract: Summary Mesophyll conductance (gm), the diffusion of CO2 from substomatal cavities to the carboxylation sites in the chloroplasts, is a highly complex trait driving photosynthesis (net CO2 assimilation, AN). However, little is known concerning the mechanisms by which it is dynamically regulated. The apoplast is considered as a ‘key information bridge’ between the environment and cells. Interestingly, most of the environmental constraints affecting gm also cause apoplastic responses, cell wall (CW) alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 91 publications
6
46
1
Order By: Relevance
“…4c). Although a coupled behaviour between g s and g m is typical during drought recovery and tissue rehydration (Flexas et al , 2012), a significant ‘uncoupling’ ( g m remained more constrained during rehydration than g s ) was found in R. myconi , suggesting important differential biochemical mechanisms driving both g s and g m (Galle et al , 2009; Clemente‐Moreno et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…4c). Although a coupled behaviour between g s and g m is typical during drought recovery and tissue rehydration (Flexas et al , 2012), a significant ‘uncoupling’ ( g m remained more constrained during rehydration than g s ) was found in R. myconi , suggesting important differential biochemical mechanisms driving both g s and g m (Galle et al , 2009; Clemente‐Moreno et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Under water deficit and salinity, g s and g m can show the same degree of limitation (observed in plants from non‐extreme environments; Flexas et al , ,b), but g m responses can differ in terms of velocity with respect to the stress, as well as during recovery after rewatering in different herbaceous and woody species (Galle et al , , ; Clemente‐Moreno et al , ). A complex behaviour of g m would also be associated with additional environmental stimuli and other traits such as water status and hydraulics (Flexas et al , ; Carriquí et al , ).…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 92%
“…The second issue is mostly related to the cell wall composition and diffusion through the cytosol and stroma (von Caemmerer and Evans, ; Flexas and Díaz‐Espejo, ). Recently, it has been reported that changes in the cell wall composition in response to stress (mostly pectins and hemicelluloses) are negatively correlated with g m , suggesting that the cell wall structure and ionic nature of the cell wall nanopores could influence the CO 2 pathway through the cell wall (Clemente‐Moreno et al , ).…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, not only the CWT but also the biochemical composition of cell walls may play roles – possibly opposite – in both CO 2 diffusion and plant water relations/desiccation tolerance. For instance, it has been recently demonstrated that either genetically (Ellsworth et al ., ) or stress‐induced (Clemente‐Moreno et al ., ) modifications in cell wall composition affect g m . Particularly pectins seem to affect negatively g m , possibly due to their anionic nature, but they are also known to be essential for modulating cell wall porosity, increase cell wall rigidity (then possibly ε) and determine the water holding capacity of cell walls (Voragen et al ., ), all of which are characters potentially related to desiccation tolerance.…”
Section: Key Role Of Mesophyll Conductance and Other Physiological Trmentioning
confidence: 99%